2002
DOI: 10.1007/s00381-001-0550-3
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular catheter placement in children with hydrocephalus and small ventricles: the use of a frameless neuronavigation system

Abstract: The usage of a neuronavigation system is safe and may be beneficial for optimal positioning and trajectory of ventricular catheters in children with small ventricles or an abnormal ventricular anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 11 publications
0
41
0
Order By: Relevance
“…Nevertheless, it appears that, as also exemplified in the present study, complications are less frequent in ventriculoperitoneal shunting than in lumboperitoneal shunting, in particular with a lower need for revision surgery during follow-up [17,18,19]. …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, it appears that, as also exemplified in the present study, complications are less frequent in ventriculoperitoneal shunting than in lumboperitoneal shunting, in particular with a lower need for revision surgery during follow-up [17,18,19]. …”
Section: Discussionmentioning
confidence: 53%
“…Both frame-based and frameless stereotactic techniques have been shown to be useful in the treatment of IIH [17,18,19] including robotic technology [20,21]. Electromagnetic (EM) navigation which can be performed without rigid head fixation has been used for various indications in neurosurgery [22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In all three types the pathophysiology consists of increased venous sinus pressure, decreased absorption of spinal CSF, increased secretion of spinal CSF, increased brain blood flow and brain edema [14] , and therefore there is no clear distinction between the above three types of disease [15] . The primary mode of therapy for patients with PC accompanied by benign intracranial hypertension and idiopathic intracranial hypertension is removal of possible etiologic causes and drainage of CSF in cases where drug therapy is ineffective [4,12,[15][16][17] . Patients who have increased intracranial pressure due to obstructed venous sinus thrombosis are usually managed by administration of anticoagulants and thrombolytic medication [16,18] .…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients with PC and high intracranial pressure it is often difficult to determine how to drain the CSF [17] . In patients with PC it has been suggested that in order to avoid brain injury due to the small size of the ventricles, CSF drainage should be conducted by an LP shunt rather than a VP shunt [5,7,8] .…”
Section: Discussionmentioning
confidence: 99%
“…The authors found improved longevity of the shunt when combined with ETV. Gil et al 4 retrospectively evaluated ventricular catheter placement with a frameless optical navigation system, but their study included only 9 patients and was excluded for having a sample size smaller than 10. McMillen et al 10 used EM image guidance for a variety of conditions in children that included only 3 cases of hydrocephalus.…”
Section: Excluded Articlesmentioning
confidence: 99%